2007
DOI: 10.1523/jneurosci.0919-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

C-Terminal Modification Is Required for GABARAP-Mediated GABAA Receptor Trafficking

Abstract: We investigated the ubiquitin-like modification of GABA A receptor-associated protein (GABARAP) and its function. A fusion protein of GABARAP with v5 in the N terminus and myc in the C terminus was expressed in rat cultured hippocampal neurons and PC12 cells. Western blotting with antibodies to v5 and myc revealed that the C terminus of GABARAP was cleaved off. Cleavage was blocked by mutating the C-terminal Gly116 to Ala, suggesting that G116 is required for the processing. Unlike ubiquitin, GABARAP was not i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
41
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 51 publications
2
41
2
Order By: Relevance
“…Indeed, LC3B can be processed by the 20S core proteasome in a ubiquitinindependent manner in vitro and this degradation is inhibited by its interaction with p62, a mediator of autophagic proteolysis [52]. Concerning GABARAP, Chen et al suggest that GABARAP does not undergo the ubiquitinylation process and is not degraded through the proteasome after lactacystin treatment in rat cultured hippocampal neurons [53].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, LC3B can be processed by the 20S core proteasome in a ubiquitinindependent manner in vitro and this degradation is inhibited by its interaction with p62, a mediator of autophagic proteolysis [52]. Concerning GABARAP, Chen et al suggest that GABARAP does not undergo the ubiquitinylation process and is not degraded through the proteasome after lactacystin treatment in rat cultured hippocampal neurons [53].…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that GABARAP contains two domains, a larger C-terminal domain (residues 27 to 117) that mediates GABA A -R binding (4,35) and a smaller N-terminal one (residues 1 to 26) that contains a novel tubulin-binding motif (7,32,35). Glycine 116 is required for the C-terminal processing of GABARAP, the localization of the protein, and its functions as a trafficking protein (5).…”
Section: Discussionmentioning
confidence: 99%
“…(A) In the absence of BDV P protein, GABA A -R is the principal GABA-gated ion channel and plays important roles in neural transmission (17). GABARAP distributes in the cytosol of the cells, interacts with the ␥2 subunit of GABA A -Rs, links GABA A -Rs to microtubules, facilitates the trafficking of GABA A -Rs to the plasma membrane (4,5), and thus enhances GABA-induced currents (10). ER, endoplasmic reticulum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HA epitope was added 5Ј to the initiation codon and c-Myc epitope immediately 5Ј to the stop codon of the cDNAs in the same vector for expression of HA-tagged or HA-and -Myc-tagged proteins. V5-GABARAP-Myc and V5-GABARAP-AL-Myc were gifts from Dr. Richard W. Olson of UCLA School of Medicine (33). For immunofluorescence microscopy and protein pulldown assays, GEC1 and GABARAP and their mutants were inserted into SalI/ XhoI sites of pCMV-HA vector (Clontech).…”
Section: Methodsmentioning
confidence: 99%